Edukasi dan Sosialisasi Pengelolaan Sampah Plastik Menjadi Ecobrick - Etika Sari; Devita Saharani; Intan Kumaladewi (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
Plastic waste is a problem that must be handled properly, because plastic waste takes a long time to decompose. The high amount of plastic waste is caused by people's dependence on plastic which is also getting bigger. One of the efforts that can be made to recycle and reduce the amount of waste in the environment is making ecobrick. Making ecobrick keeps waste in bottles so that people don't have to burn, hoard or litter. PkM activities carried out by providing socialization and education on plastic waste management. The aim of this PkM is to provide knowledge and insight to the community in reusing plastic waste through ecobrick. The results of the education that has been carried out can increase the knowledge and awareness of the community regarding the management of plastic waste into ecobrick as goods that have high use value such as being used for making walls on a larger scale and has the potential to increase the economic value of waste.